Risk factors associated with COVID-19 severity among patients on maintenance haemodialysis: a retrospective multicentre cross-sectional study in the UK. Issue 5 (30th May 2022) - Selvaskandan, Haresh; Hull, Katherine L; Adenwalla, Sherna; Ahmed, Safa; Cusu, Maria-Cristina; Graham-Brown, Matthew; Gray, Laura; Hall, Matt; Hamer, Rizwan; Kanbar, Ammar; Kanji, Hemali; Lambie, Mark; et al.
Abstract : Objectives: To assess the applicability of risk factors for severe COVID-19 defined in the general population for patients on haemodialysis. Setting: A retrospective cross-sectional study performed across thirty four haemodialysis units in midlands of the UK. Participants: All 274 patients on maintenance haemodialysis who tested positive for SARS-CoV-2 on PCR testing between March and August 2020, in participating haemodialysis centres. Exposure: The utility of obesity, diabetes status, ethnicity, Charlson Comorbidity Index (CCI) and socioeconomic deprivation scores were investigated as risk factors for severe COVID-19. Main outcomes and measures: Severe COVID-19, defined as requiring supplemental oxygen or respiratory support, or a C reactive protein of ≥75 mg/dL (RECOVERY trial definitions), and its association with obesity, diabetes status, ethnicity, CCI, and socioeconomic deprivation. Results: 63.5% (174/274 patients) developed severe disease. Socioeconomic deprivation associated with severity, being most pronounced between the most and least deprived quartiles (OR 2.81, 95% CI 1.22 to 6.47, p=0.015), after adjusting for age, sex and ethnicity. There was no association between obesity, diabetes status, ethnicity or CCI with COVID-19 severity. We found no evidence of temporal evolution of cases (p=0.209) or clustering that would impact our findings. Conclusion: The incidence of severe COVID-19 is high among patients on haemodialysis; this cohort should be considered high risk. There was strong evidence of an association between socioeconomic deprivation and COVID-19 severity. Other risk factors that apply to the general population may not apply to this cohort.